2001
DOI: 10.1104/pp.126.2.601
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Isovaleryl-Coenzyme A Dehydrogenase of Arabidopsis Oxidizes Intermediates of Leucine and Valine Catabolism

Abstract: We recently identified a cDNA encoding a putative isovaleryl-coenzyme A (CoA) dehydrogenase in Arabidopsis (AtIVD). In animals, this homotetrameric enzyme is located in mitochondria and catalyzes the conversion of isovaleryl-CoA to 3-methylcrotonyl-CoA as an intermediate step in the leucine (Leu) catabolic pathway. Expression of AtIVD:smGFP4 fusion proteins in tobacco (Nicotiana tabacum) protoplasts and biochemical studies now demonstrate the in vivo import of the plant isovaleryl-CoA dehydrogenase (IVD) into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 37 publications
4
98
0
Order By: Relevance
“…In Arabidopsis, isovaleryl-CoA dehydrogenase is localized in plant mitochondria (Daschner et al, 2001;Taylor et al, 2004), and our metabolite profiling data ( Figure 5) demonstrated a marked accumulation of the isovaleryl-CoA dehydrogenase substrate, isovaleryl-CoA, in etfqo mutants, suggesting dysfunction of isovaleryl-CoA dehydrogenase in these mutants. These results further support the existence of the electron transfer cascade from isovaleryl-CoA dehydrogenase to ETF, ETF to ETFQO, and ETFQO to ubiquinone in the electron transport chain of plant mitochondria as reported in mammals , although the direct interaction of these four components has yet to be confirmed.…”
Section: Involvement Of Etfqo In Leu Catabolismmentioning
confidence: 97%
See 2 more Smart Citations
“…In Arabidopsis, isovaleryl-CoA dehydrogenase is localized in plant mitochondria (Daschner et al, 2001;Taylor et al, 2004), and our metabolite profiling data ( Figure 5) demonstrated a marked accumulation of the isovaleryl-CoA dehydrogenase substrate, isovaleryl-CoA, in etfqo mutants, suggesting dysfunction of isovaleryl-CoA dehydrogenase in these mutants. These results further support the existence of the electron transfer cascade from isovaleryl-CoA dehydrogenase to ETF, ETF to ETFQO, and ETFQO to ubiquinone in the electron transport chain of plant mitochondria as reported in mammals , although the direct interaction of these four components has yet to be confirmed.…”
Section: Involvement Of Etfqo In Leu Catabolismmentioning
confidence: 97%
“…Such a hypothesis is consistent with the observations that the peroxisomal short-chain acyl-CoA oxidase is able to oxidize isobutyryl-CoA (Hayashi et al, 1999), and the demonstration that several other enzymes involved in Ile and Val catabolism are localized in peroxisomes in Arabidopsis (Lange et al, 2004;Taylor et al, 2004). The mitochondrial isovaleryl-CoA dehydrogenase does utilize 2-methyl-butyryl-CoA as a substrate in vitro; however, the K m value of the enzyme for the isobutyryl-CoA is ;10 times larger than that for isovaleryl-CoA (Daschner et al, 2001). Since the relative concentration of Val is only half that of Leu, the large difference in K m values suggests that isovalerylCoA dehydrogenase is not involved in Val oxidation in vivo.…”
Section: Involvement Of Etfqo In Leu Catabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…The insert was removed from this plasmid by digestion with XbaI and SmaI and cloned in frame upstream of the GFP gene in the vector psmGFP4 (Davis and Vierstra, 1998). Transformation of tobacco (Nicotiana tabacum) protoplasts and fluorescence microscopy were done as described before (Koop et al, 1996;Dä schner et al, 2001;Diebold et al, 2002). All standard methods used were performed according to established protocols (Sambrook et al, 1989).…”
Section: Miscellaneuos Methodsmentioning
confidence: 99%
“…This polypeptide stimulates in vitro transcriptional activity from a wheat cox2 mitochondrial promoter and is thus a very promising candidate for a bona fide promoterbinding protein. In pea (Pisum sativum) a 43 kDa protein was purified from mitochondria by its promoter-binding properties, which shows high similarity to isovaleryl CoA dehydrogenase enzymes from other organisms (Däschner et al 2001 could be an interesting example of a dual-function protein, which could connect metabolic activities and requirements with gene expression in mitochondria. Such bifunctional molecular connections have been identified in yeast mitochondria, where several proteins are involved in gene expression, as well as in metabolic and energytransforming processes.…”
Section: Rna Polymerase and Its Cofactorsmentioning
confidence: 99%